A Comprehensive Evaluation of Driver Tendencies and Roadway Use Using Bluetooth Technology - Sebens, Justin D. (My University, 2013)
The Madison Beltline Highway (USH 12/14/18/151) is the only freeway arterial around the southern portion of Madison, Wisconsin. During the planning stages of the roadway, it was design to be an alternative route so that drivers could avoid the congested streets of the downtown area and so trucks and bypass traffic could stay off the main streets. As with many highways in an urban area, once it was built, urban sprawl built up around the highway. Today the Beltline is one of the most heavily traveled roads in the southwestern part of the state. The Beltline experiences weekday AM and PM peak delays, as well as intermitted delays during special events such as Badger football/basketball games. This research looks at the current origin-destination travel patterns of the Beltline highway. Specifically, the main objectives of this research were to show that Bluetooth origin ? destination (O-D) is a cost effective alternative to traditional O-D data collection methods, to analyze and explain driver patterns and the current use of the Beltline highway in Madison Wisconsin. Bluetooth technology is a new way to collect traveler information. It is able to collect travel times, speeds, and if multiple units are used, O-D data. These detectors work by matching Bluetooth Media Access Control (MAC) IDs between multiple stations with known locations to calculate travel times, speeds, and O-D. A four step methodology was used to complete the objectives above. The first step in the methodology was a pilot study completed at the Beltline?s Fish Hatchery Road interchange in July 2012. The pilot was completed to determine if the sample O-D closely matches the population O-D when analyzing the percentage of vehicles making a specified movement. Once completed and confirmed that the Bluetooth sample did indeed replicate the population data, it was concluded that a large scale O-D was feasible using Bluetooth technology. Traffax Bluetooth devices were placed along the Beltline, interchange approaches, and Dane County for 6 weeks starting in August and continuing into October. Data from this regional O-D study completed by TADI, a Wisconsin traffic engineering consulting company, was reduced to a workable data set and then processed to produce driver traces and O-D Tables for the Beltline. Once produced, these traces and O-D Tables were used to analyze and produce driver tendency charts for the days of August 20th-24th and September 10th-14th, 2012. The driver tendency charts correlate to the percentage of traffic that exits the Beltline if they originate at a specific interchange. Unlike traditional O-D using nodes, Bluetooth O-D can pinpoint where the vehicle went when it exited the Beltline and use the same detector to detect a vehicle entering the Beltline, reducing the equipment costs needed for the O-D. The patterns or driver tendencies produced by the data show that the use of the Beltline has changed over the decades since it was first designed and opened for travel in the late 1940s early 1950s as a two lane highway. In the late 1960s the DOT unveiled a 10 year project to upgrade the Beltline to a six lane freeway. The patterns and commuter percentages also show that the use changes depending on where the drivers enter the Beltline (the specific interchange). The research results show that Bluetooth sample O-D closely matches the population O-D patterns. Therefore, one can conclude that Bluetooth O-D can be used as a cost effective method for future O-D studies as compared to traditional methods. The lessons learned showed that due to the variability in Bluetooth data one must be careful when using sample sets with low numbers. This technique is not ideal for low volume roadways. Lastly, Bluetooth O-D is a viable cost effective method when sample sizes are adequate.